Investigating the Practices of Project Governance in Public Sector Infrastructure Program in Pakistan - Khan, Asadullah; M., Waris; Ishak, Ismail; Mirza, Rizwan Sajid; Ali, Zaigham; Ullah, Mehfooz; Hussain, Ammar (Hindawi, 2019)
The governance of public sector infrastructure projects became an important area of interest in the literature on project management. Today, it is a focal point for policymakers to ensure successful appraisal and implementation of government-sponsored programs. This paper aims to investigate the current practices of project governance (PG) for steering the public sector infrastructure program in Pakistan. An empirical investigation was carried out among professionals of public sector organizations involved in different infrastructure development projects. Latent construct of PG was validated through second-order confirmatory factor analysis (CFA) and quantified the three dimensions of PG, i.e., portfolio direction (PD), sponsorship, effectiveness, and efficiency (SEE), and disclosure and reporting (DR) through the relative importance index (RII) method. The result showed that DR is among the least practicing dimension having RII = 0.55, while PD and SEE have shown similar prevalence with RII = 0.70 and 0.69, respectively. Overall, the most practicing item in the PG was “the alignment of portfolios with objectives and strategy” whereas the lowest practicing item relates to the “completeness of project information distribution due to the multi-layered bureaucratic system.” The findings of this study will guide the decision makers to take appropriate measures for enhancing the effectiveness of PG in Pakistan.